PENGARUH LEVERAGE, INTENSITAS MODAL, KOMPENSASI RUGI FISKAL, FAMILY CONTROL, FAMILY MANAGEMENT TERHADAP TAX AVOIDANCE (Studi Kasus Pada Perusahaan Manufaktur Sub Sektor Industri Dasar dan Kimia Periode 2017 – 2020) - Dita Dwijayanti; Muhammad Astri Yulidar Abbas; Novi Yanti (University of Widya Gama Mahakam Samarinda, 2022)
This study aims to determine the effect of Leverage, Capital Intensity, Fiscal Loss Compensation, Family Control, Family Management on Tax Avoidance. The method used in this study is a quantitative method, while data collection is taken from the Annual Report in this study using purposive sampling. The data analysis technique used is multiple linear analysis. The sample used in this study were 23 basic and chemical manufacturing industry sectors listed on the Indonesia Stock Exchange for the period 2017 – 2020. The data analysis technique used was multiple linear regression analysis. The results of this research analysis that Leverage has no effect on Tax Avoidance, Capital Intensity has a negative effect on Tax Avoidance, Fiscal Loss Compensation has no effect on Tax Avoidance, Family Control cannot be analyzed because it has no data variance, and Family Management has no effect on Tax Avoidance. Keywords: Tax Avoidance, Leverage,Fiscal Loss Compensation, Family Control, Family Management on Tax Avoidance.